Cultural property crime : an overview and analysis on contemporary perspectives and trends - Kila, Joris.; Balcells, Marc. (Heritage and Identity, 2015)
In Cultural Property Crime various experts in the fields of criminology, art law, heritage studies, law enforcement, forensic psychology, archaeology, art history and journalism provide multidisciplinary perspectives on today's concept of cultural property crime, including art crime. In addition, the volume deals with international, legal and practical developments regarding the increasing criminalization of acts against cultural property in times of conflict. Attention is paid to the changing status and fluctuating appraisal of cultural property as subject to classical art crimes generally in peacetime and as an identity-related symbolic target during conflict. The book covers a wide range of topics such as forgeries, white-collar crime, archaeological looting and the impact of war on cultural heritage. ALSO AVAILABLE IN PAPERBACK at a reduced price!